Pristranosti interneta in (ne)moč spletnih občinstev - Oblak, Tanja (Družboslovne razprave, 2012)
The main purpose of this article is to set out the main limitations of the "emancipatory" potential of the Internet, and to show certain biases of this technology with regard to audiences and individual agency online. The text first conceptualises cyberspace as an assemblage of material infrastructure, public representations and everyday practices which enables the differentiation of the key levels through which relations among different actors on the Web are formed. The authors then provide a critique of technological determinism by focusing on their own model of material, incorporated and structural biases that constrain the power of audiences and possible emancipatory potential that could develop online. While material biases derive from the technical infrastructure of the Web that is based on network structure and web links, embedded biases refer to digital competencies, the homogenization of choice and mechanisms of authority. When it comes to structural biases, crucial areas include commodification, privatisation and concentration which are transmitted via both the technical infrastructure as well as content and applications. The authors conclude with a consideration of the possible consequences of these findings for understanding the complicated relations involved in studying audiences on the Web.
Keywords: Svetovni splet; World Wide Web; Digital media; Elektronski mediji; Kibernetski prostor; Cyberspace; Občinstvo; Audiences; Autonomy; Avtonomija; internet